W zwierciadle opcji politycznych. Perswazyjność komunikacji politycznej na przykładzie analizy debat plenarnych w Parlamencie Europejskim - Wypiorczyk, Agnieszka (Lustro, 2020)
The main focus of the article is the political communication. The analysis of the speeches given by the members of European Parliament at plenary debate shows how politicians address the same issues, while presenting them from the perspective of the political beliefs, which they represent. In addition, in order to examine the persuasiveness of political communication at plenary debate, the article focuses on analysis of the persuasive strategies used in the statements of Members of European Parliament.